STUDENT GRAPHICAL INFORMATION LITERACY IN MATHEMATICS AND SCIENCE - France, Ilze; Namsone, Dace; Čakāne, Līga; Vilciņš, Jānis; Dzērve, Uldis; Nikolajenko, Andris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Among the most important 21st century skills that every student needs are the ability to work with information. The key for implementing competency based approach to learning will be related to how students' ability to apply skills acquired in, for example, mathematics can be transferred to other subject contexts. Newest OECD PISA results presented in 2016 show a recurring tendency that in Latvia there is a small number of students whose performance is in accordance to the 5th and 6th level of the framework. These two levels represent students' ability to apply deep thinking skills in new learning contexts. It is necessary to analyze the causes of this situation in order to identify opportunities for how to improve student performance. Accordingly, the research goal is to analyze how Latvian students manage to apply deep thinking skills in 9th grade national test assignments where they need to analyze graphic information in science and real life context. Additionally, the research aims to analyze the cognitive depth of science and mathematics assignments included in the national test as well as how the acquisition of these skills are planned in the learning content of educational regulations and learning materials.